1975
DOI: 10.1002/prac.19753170109
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophile Substitutionen an Kohlensäurederivaten. V. Kinetik und Mechanismus der Äthanolyse von Kohlensäure‐arylester‐chloriden

Abstract: Es wurden die Geschwindigkeitskonstanten pseudo‐erster Ordnung für die Äthanolyse von Kohlensäure‐arylester‐chloriden in Äthanol‐Aceton (35:65, V/V) und in reinem Äthanol bestimmt. Es konnte ein Additions‐Eliminierungsmechanismus ähnlich dem bei der Hydrolyse in Wasser‐Aceton (35 Vol.‐% H2O) festgestellt werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1975
1975
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Noting that similar behaviour in related solvolyses of diaryl carbonates had been corrected 32 by use of the 'normal' σ 0 values of Taft 33 (established using substrates with isolated substituted phenyl groups, with no resonance interaction 33-35 ), they also substituted σ 0 values for the original σ values and found that a good linear relationship (ρ = 1.03) then resulted. Parallel behaviour was found in 65% acetone 6 (ρ = 1.59) and ethanol 18 (ρ = 1.73). Therefore, it appears that, with use of the appropriate substituent constants, one good linear relationship is obtained for solvolyses over the full range of substituted phenyl chloroformates (substituents ranging from p-benzyloxy to p-nitro), consistent with an essentially constant reaction mechanism not only over a wide range of solvents but also over a wide range of ring substituents.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Noting that similar behaviour in related solvolyses of diaryl carbonates had been corrected 32 by use of the 'normal' σ 0 values of Taft 33 (established using substrates with isolated substituted phenyl groups, with no resonance interaction 33-35 ), they also substituted σ 0 values for the original σ values and found that a good linear relationship (ρ = 1.03) then resulted. Parallel behaviour was found in 65% acetone 6 (ρ = 1.59) and ethanol 18 (ρ = 1.73). Therefore, it appears that, with use of the appropriate substituent constants, one good linear relationship is obtained for solvolyses over the full range of substituted phenyl chloroformates (substituents ranging from p-benzyloxy to p-nitro), consistent with an essentially constant reaction mechanism not only over a wide range of solvents but also over a wide range of ring substituents.…”
Section: Discussionsupporting
confidence: 52%
“…The most thorough study is presented in two papers by Bacaloglu and co-workers. 6, 18 For the parent phenyl chloroformate and eleven ring-substituted derivatives, they obtained a good linear plot against the traditional Hammett σ values for solvolyses in 10% aqueous acetone, 6 except that the data points for the p-methoxy and, especially, the p-benzyloxy substituents lay above the plot. Noting that similar behaviour in related solvolyses of diaryl carbonates had been corrected 32 by use of the 'normal' σ 0 values of Taft 33 (established using substrates with isolated substituted phenyl groups, with no resonance interaction 33-35 ), they also substituted σ 0 values for the original σ values and found that a good linear relationship (ρ = 1.03) then resulted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other techniques had previously been applied to studies of the solvolyses of phenyl chloroformate, including F/Cl leaving group effects, , Hammett treatments of substituent effects, solvent isotope effects, and consideration of the activation parameters. These techniques have all indicated a bimolecular mechanism, almost certainly of the addition−elimination (tetrahedral intermediate) type (eq 2) but possibly with the first-formed intermediate so unstable that the mechanism could be considered 8 as an enforced concerted variant …”
mentioning
confidence: 99%